Application of Synergetic Teaching Type Cooperative Learning Model to Improve Students' Reading Comprehension Ability - Marleni, Lusi; Yenita, Resi; Novita, Rusma; Perwita, Santi Indah; Simanjuntak, Sapta Lamsihar; Ningsih, Sisca; Solihin, Solihin; Andayani, Sri; Syafrianengsih, Syafrianengsih; Harianti, Tuti; Leoni, Yalen; Hasibuan, Yusnah (Journal of English Language and Education, 2024)
This study aims to improve the reading comprehension ability of grade IV students of State Elementary School 007 Rimbo Panjang through the application of a Synergetic Teaching type cooperative learning model. This model provides students with the opportunity to learn collaboratively by comparing their understanding of the same material. The research method used is Classroom Action Research (PTK) with two cycles, where each cycle consists of planning, action, observation, and reflection. Data was collected through observation, learning outcome tests, and interviews. The results showed that before the implementation of the Synergetic Teaching model, students' reading comprehension ability was relatively low with an average of 65.3%. After the first cycle, there was an increase to 73.3% (medium category). In the second cycle, the average score increased significantly to 86.1% (high category). In addition, observations show that student activity and engagement in learning also increase. The conclusion of this study is that the Synergetic Teaching type cooperative learning model is effective in improving students' reading comprehension skills. Therefore, it is recommended that teachers apply this model in learning to read and understand and adapt it to other subjects to improve student learning outcomes